PEMANFAATAN LIMBAH DAUN HASIL PENYULINGAN MINYAK KAYU PUTIH MENJADI BRIKET ARANG DI DESA WAIMITINGKABUPATEN BURU - Idrus Hentihu; Iskandar Hamid, Muhammad Bula, Muhammad Taufik, RH Fitri Faradilla (Prosiding Seminar Nasional Indonesia, 2025)
Waimiting is one of the villages in Lilialy District, Buru Regency, Maluku, Indonesia.Most of the area of Waimiting Village consists of eucalyptus plantations. The majority of the people of Jajaran Baru Village work as eucalyptus oil refiners. Waimiting Village is a partner village in the 2024 Kosabangsa Program activities with activities in the form of socialization and training in making briquettes from leaf waste from eucalyptus oil distillation as an effort to reduce leaf waste from eucalyptus oil refining and train the community in processing eucalyptus oil distillation leaf waste as an alternative energy source. Based on the results of these activities, results were obtained in the form of increasing the knowledge and skills of partners in making briquettes using eucalyptus oil distillation leaf waste. From the analysis data, an average score of 88.9 was obtained, which shows that public knowledge about briquettes from eucalyptus oil distillation leaf waste as an alternative energy is included in the Very Good category. For community skills, the average score was 88.7, this shows that community skills are in the Very Good category.